Pengaruh Lingkungan Kerja, Beban Kerja dan Kompensasi Terhadap Turnover Intention Pada PT. Intan Hevea Industry - Evelina, Febry; Sari, Tika Nirmala (ProBisnis : Jurnal Manajemen, 2025)
The study aims to determine and analyze the influence of consumer This study aims to determine the influence of the work environment, workload, and compensation on turnover intention at PT. Intan Hevea Industri. This study employed quantitative research. Data sources used were primary and secondary data. Data collection techniques included questionnaires, interviews, and documentation. Data analysis techniques used were descriptive statistics, classical assumption tests, multiple linear regression, and hypothesis testing. The sample size for this study was 93 respondents. The partial test results revealed that the work environment had a positive and significant effect on turnover intention, with a t-value of 3.461 > 1.986. Workload had no positive and significant effect on turnover intention, with a t-value of 1.760 < 1.986. Compensation had a positive and significant effect on turnover intention, with a t-value of 3.670 > 1.986. Based on the simultaneous test results, it was found that the work environment (X1), workload (X2), and compensation (X3) variables simultaneously had a positive and significant effect on employee turnover intention at PT. Intan Hevea Industry.